Fonem Deret Konsonan dalam Bahasa Indonesia - Ary Setyadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The existence of consonant series phonemes in Indonesian phonological learning is important, but strangely it has not received special attention, so it is interesting to be the object of study. Based on existing data, if we find a phoneme study of consonant series from several references, it turns out that the discussion is only a part / sub-section of the subject matter of the study. The application of theory is based on the linguistic theory of phonological branches, phonemic subcabang, because the study focuses on the phoneme of the consonant series itself and its ability to form consonant sequences. The implementation of the study starts at three strategic stages as in linguistic research in general, namely: 1. the stage of providing data, 2. the stage of classification and analysis of data, and 3. the stage of preparing the report. The phoneme data of consonant series is more secondary, so the existence of references is a data source. The results of the consonant phoneme data analysis almost apply to all consonant phonemes in Indonesian, including loan / absorption (foreign) phonemes. The basis for determining the consonant phoneme starts with: 1. a consonant series is a consonant series of two / or more phonemes in one word, but in different syllables; 2. consonant phoneme data departs from the kinds of vocabulary in Indonesian; and 3. that the question of syllable decapitation is based on decapitation of the word form (morphological), not on sound (phonological) elements. The types of vocabulary used as data include: 1) original Indonesian vocabulary; 2) loan / absorption vocabulary, especially from the process